The possibility of detecting non-x-ray fragments in the body of the wounded by the contact method - Oleksandr Salenko; Yuriy Danylchenko; Viktor Cherniak; Vadym Orel; Valentyna Datsenko; Bohdan Salenko; Kostiantyn Karpenko (Mechanics and Advanced Technologies)
The types of injuries and types of striking elements were analyzed, the conditions of patients requiring urgent surgical intervention were assessed. The possibilities of existing means of diagnosing fragments in the patient's body were analyzed, and it was concluded that for non-X-ray contrast fragments, the proposed method of mechanical contact with a special flexible and elastic probe is appropriate and effective. A special tool for examining wound canals has been developed, consisting of a flexible probe for individual use and a handle-holder with a microphone capsule, the membrane of which is directly connected to the probe and reacts to mechanical contact with an obstacle, and the capsule itself is directly connected to the oscilloscope through a signal amplifier . which has spectral signal processing circuits. The problem of the interaction of the elastic contact of a non-rigid element with a fragment located in a viscous medium is set, provided that the properties of the medium are not constant. Typical solutions of this problem for various types of fragments and parameters of the contacting element itself are presented. A picture of the noise emission accompanying the contact is shown. The functional dependence of noise emission parameters on the shape and type of the foreign object in the wound canal was revealed. The expediency of using the frequency-amplitude characteristic of noise radiation as a controlled parameter has been proven. A conclusion was made about the functional conditioning of the width of the signal spectrum and basic frequencies at the time of mechanical contact with a foreign object in the wound, depending on its shape and type; it was established that the use of an oscilloscope with a spectral analysis channel allows for the fairly accurate identification of a non-radiocontrast foreign object in a wound.